Analysis of the Effect of Education, Labor, and Population on Poverty in Jambi Province - Revadila, Siti Nurani; Putra, Adi; Winarni, Etik (Jurnal Prajaiswara, 2026)
Introduction/Main Objectives: This study aims to analyze the effect of education, labor, and population on poverty levels in Jambi Province during the 2015–2025 period. Background: Poverty is a multidimensional issue influenced by various economic and social factors. Education, labor, and population are often considered key determinants affecting societal welfare and poverty dynamics in a region. Novelty: This study provides a recent empirical analysis using time-series data from 2015–2025 in Jambi Province and examines both partial and simultaneous effects of the three main variables in explaining poverty variation. Research Method: This study employs a quantitative approach using multiple linear regression analysis. Hypothesis testing is conducted using the t-test for partial effects and the F-test for simultaneous effects at a significance level of 5% (α = 0.05). Findings/Results: The results show an R² value of 0.655, indicating that 65.5% of the variation in poverty is explained by the independent variables. The correlation coefficient (R) of 0.809 indicates a strong relationship. Partially, education (-2.450; Sig. 0.633), labor (0.010; Sig. 0.889), and population (-0.078; Sig. 0.221) have no significant effect. However, simultaneously, all variables significantly influence poverty. Conclusion: Poverty in Jambi Province is influenced not only by education, labor, and population but also by other factors outside the model. Therefore, comprehensive and integrated policies are needed to effectively reduce poverty.